Pricing Fund Liquidity Provision - Rossi, Marco (Washington, D.C. : International Monetary Fund, 2007)
This paper presents a market-based framework for pricing Fund liquidity assistance that accounts for the credit risk and the insurance benefit involved in such operations. It is based on the isomorphic correspondence between Fund liquidity and common stock put options. Although only illustrative, the simulations presented in this paper show that the value of the liquidity guarantee provided by the Fund could range from a few to over one hundred basis points depending on the borrower's creditworthiness, the volatility of capital flows to the borrowing country, and the amount of funds potentially needed to meet the borrower's external obligations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet